Experiences of 5th year students in Kerbala with formative mini-CEX - alzubaidi, riyadh dhayhood (Karbala Journal of Medicine, 2019)
Background Formative work place assessment give opportunities to follow the progression of students learning through monitoring of their doing Aim To know the experience of the 5th year students with the first year implementation of formative mini clinical evaluation exercise (mini-CEX). Method & participants It is a qualitative research. The information were collected from interview with students completed the internal medicine discipline of the fifth year during the academic year 2017 - 2018. Results The participants were aware about the exam, the embarrassment of the exam and the presence of peer get less with subsequent examinations, and the encouraging feedback of the examiner exerted a positive effects on the learning process. The students explored the need to further training of clinical examination, in addition to adhering to instructions regarding the need to focus on educational goals. Some of the teachers did not administer the exam according to the instructions of mini – CEX. Conclusion The experience resulting from the mini clinical evaluation exercise (mini-CEX) indicates positive results with regard to studentsʹ rush towards learning, a great opportunity for teachers to follow up the studentsʹ level and guidance, enhancement the studentsʹ communication skills, and the need of some teachers to adhere to the essence of this type of assessment.